High efficiency ternary organic solar cell with morphology-compatible polymers. Issue 23 (28th February 2017) - Mai, Jiangquan; Lu, Haipeng; Lau, Tsz-Ki; Peng, Shih-Hao; Hsu, Chain-Shu; Hua, Wenqiang; Zhao, Ni; Xiao, Xudong; Lu, Xinhui
Abstract : The short circuit current density and fill factor are improved in ternary organic solar cell due to the high morphology compatibility. Abstract : Ternary organic solar cell is a promising strategy for improving the power conversion efficiency (PCE) of single-junction organic solar cells by broadening the light absorption spectrum with the incorporation of two electron donors and one acceptor or one donor and two acceptors. However, in many cases the optimized loading of the third component is so small that its contribution to the light absorption is limited. Following our previously proposed selection rule for the two polymers capable of comparable loadings, we report in this work a ternary system composed of two morphologically compatible polymers with distinct chemical structures that can achieve a high PCE of 9.0% with a mass ratio of 1 : 1. Besides the expected improvement in short circuit current due to the broadening of the absorption spectrum, the fill factor of the ternary device is improved significantly. We attribute it to the balanced electron and hole mobility and reduced recombination benefiting from the high morphology compatibility of the system.